P9 Hyperpolarised ketone body metabolism in the rat heart. (21st March 2018) - Miller, JJ; Ding, YB; Ball, D; Lau, AZ; Tyler, DJ
Abstract : Hyperpolarised Magnetic Resonance Spectroscopy (MRS) permits the real time determination of metabolic fluxes in the living heart. In contrast to conventional thermal-equilibrium MRS, the hyperpolarisation technique increases the signal-to-noise ratio of acquired spectra by many orders of magnitude, and therefore allows isotopically labelled probes to be injected into an organism and followed through their subsequent biochemical pathways. We show here that [1–13C]acetoacetate and [1–13C]β-hydroxybutyrate can be hyperpolarised and probe ketone body metabolism in both the ex vivo perfused and in vivo rat heart. Downstream metabolites were observed within the perfused heart, including acetylcarnitine, citrate, and glutamate. In the in vivo heart, a statistically significant increase in acetylcarnitine production from acetoacetate was observed in the fed state, as well as a potential reduction in glutamate, when compared to fasted controls. The metabolism of acetoacetate and β-hydroxybutyrate is known to be altered in various disease states, including diabetic cardiomyopathy, and this proof-of-principle study shows that hyperpolarisation can probe the role of ketone bodies in the diseased heart. The increased rate of acetylcarnitine production following feeding is consistent with its reported role as a store of acetyl moieties should they be abundant in a post-prandial state, into which ketone oxidation is directed. In the fasted state, apparent glutamate levels were higher, which is consistent with an increased flux of ketone bodies into the TCA cycle during fasting. Further work will aim to quantify these fluxes, and explore the role of ketone bodies in animal models of cardiac disease, such as diabetic cardiomyopathy.